Teachers’ Perceptions of Providing Feedback in Application-Based Writing EFL Classrooms - Triyuana Nikmatul Fadzilah; Nuskhan Abid (English Department, Universitas Negeri Surabaya, 2026)
This study aims to explore EFL teachers’ experiences with app-based feedback, specifically how they perceive its benefits, address the challenges, and employ strategies in this practice. This study employs a phenomenological qualitative design to explore teachers’ experiences and interpretations of using apps to provide feedback in writing classes. The research participants were EFL lecturers at a state Islamic university in Central Java, selected through purposive sampling based on their experience in teaching writing and using app-based feedback. Data were collected through semi-structured interviews with open-ended questions and analyzed using thematic analysis. The results revealed three main themes: (1) the benefits of using applications to provide feedback in EFL writing classes, (2) challenges in implementing application-based feedback in EFL writing classes, and (3) teachers’ strategies for providing application-based feedback in EFL writing classes. The findings indicate that the app facilitates the provision of more detailed, structured, and easily accessible feedback to students. However, there are several challenges, including time constraints, technical difficulties, variations in students’ digital literacy, and potential misunderstandings about written feedback. To address these issues, teachers employ various strategies, such as focused feedback, a combination of direct and indirect feedback, and balanced feedback that combines corrective comments with praise. Overall, this study indicates that using the app can enhance the effectiveness of feedback delivery; however, its success remains dependent on technological readiness and appropriate pedagogical strategies.